Reproductive histology of the saddled seabream Oblada melanura in the southern Mediterranean Sea (Tunisian coast) - Kalai Saoussen; Khoufi Widien; Meriem Sadok Ben (Oceanological and Hydrobiological Studies)
The saddle seabream, Oblada melanura, is an important species in Mediterranean coastal fisheries. The artisanal gillnet fishery on Tunisia’s northern coast was sampled on a monthly basis between April 2015 and March 2016. The sex ratio varied by month throughout the year, with females dominating from November to December and equal sex ratios during the rest of the year. For both sexes, gonad maturity and gonadosomatic index (IG) indicated that spawning occurs from May to September. In terms of energy investment, fish feed throughout the year. During the spawning period (May to September), gonadal production (IG) appears to be supported by liver reserves (IH). These reserves came from external sources (i.e. food) in the period before spawning. During the spawning period, it was necessary for the fish to continue feeding in order to support their body development. Estimated lengths at 50% maturity were similar for females (L50 = 17.14 cm) and males (L50 = 17.01 cm).